2017
DOI: 10.1113/ep086573
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular acidosis selectively inhibits pharmacomechanical coupling induced by carbachol in strips of rat gastric fundus

Abstract: What is the central question of this study? Acute acidosis that results from short-term exercise is involved in delayed gastric emptying in rats and the lower responsiveness of gastric fundus strips to carbachol. Does extracellular acidosis decrease responsiveness to carbachol in tissues of sedentary rats? How? What is the main finding and its importance? Extracellular acidosis inhibits cholinergic signalling in the rat gastric fundus by selectively influencing the G protein signalling pathway. Acute acidosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…In this sense, we recently reported that acute exercise delays the gastric emptying rate in rats, a phenomenon prevented by bicarbonate treatment. In addition, extracellular acidosis in vitro inhibits cholinergic neurotransmission in the rat gastric fundus by selectively influencing the Gq/11 protein-signaling pathway (22,23). Now, we report for the first time the morphofunctional modifications in the intestinal barrier, such as increased intestinal permeability associated with changes in the transcription of a tight junction (claudin-2) in a physically exhaustive test, which was prevented by AG treatment.…”
Section: Discussionmentioning
confidence: 75%
“…In this sense, we recently reported that acute exercise delays the gastric emptying rate in rats, a phenomenon prevented by bicarbonate treatment. In addition, extracellular acidosis in vitro inhibits cholinergic neurotransmission in the rat gastric fundus by selectively influencing the Gq/11 protein-signaling pathway (22,23). Now, we report for the first time the morphofunctional modifications in the intestinal barrier, such as increased intestinal permeability associated with changes in the transcription of a tight junction (claudin-2) in a physically exhaustive test, which was prevented by AG treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Carbachol (CCh) is a cholinergic agonist that binds to muscarinic receptors coupled to the G protein, specifically Gq/11, which releases calcium and consequently elicits smooth muscle contraction (Silva et al, 2014;Oliveira et al, 2017). Regarding the CCh responsiveness protocol of gastrointestinal tissues, there was a shift to the right of the contractility curve of the duodenum strips in 2K1C rats, indicating reduced responsiveness to the CCh cholinergic agonist.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently showed that pharmacomechanical stimulation induced by cholinergic signaling through muscarinic receptors is affected by extracellular acidosis in isolated preparations of rat gastric fundus (40). This phenomenon could also be involved in the exercise-induced gastric emptying delay in rats (i.e., a condition that causes lactate-derived extracellular acidification) (7).…”
Section: Discussionmentioning
confidence: 99%